Modular multi-input converter design for hybrid energy storage system used in traction power substation - Toh, Chuen Ling; Tan, Ching Sin; Tan, Chee Wei (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
Hybrid energy storage system (HESS) which consists of battery and supercapacitor is proposed to store bulk regenerative braking energy for future traction power substation. This system aims to optimize energy utilization and enhance the sustainability of rail transport. To facilitate bidirectional power flow between the traction network and the HESS, this paper introduces a modular multi-input converter (MMIC) to dynamically transfers during both braking and acceleration phases of train operation. The proposed MMIC operates in multiple modes, allowing for seamless energy exchange between the battery and supercapacitor, thus minimizing the depth of discharge of the battery and extending its lifespan. A comprehensive theoretical analysis of the MMIC is presented, detailing its four distinct operating modes. Additionally, simulation model of a 1.5 kV traction power substation with 500 kWh HESS is developed to validate the performance of the MMIC during steady-state operation. The findings demonstrate significant improvements in energy recovery and storage capabilities, underscoring the potential of the HESS to support future traction power substations in achieving higher efficiency and sustainability.